Resveratrol Treatment of Autism Spectrum Disorder—A Pilot Study. Issue 5 (7th September 2022) - Marchezan, Josemar; Deckmann, Iohanna; da Fonseca, Guilherme Cordenonsi; Margis, Rogerio; Riesgo, Rudimar; Gottfried, Carmem
Abstract : Objectives: Considering autism spectrum disorder (ASD) as a neurodevelopmental condition associated with immune system impairments, we aimed to evaluate the potential benefits, efficacy, tolerability, and safety of the anti-inflammatory, antioxidant, and neuroprotective trans -resveratrol (RSV) in behavioral impairments and in a set of 8 microRNAs (miR) related to the immune system in pediatric subjects with ASD. Methods: This is an open-label pilot trial over a 3 months (90 days) study follow-up period designed to assess the effect of 200 mg/d RSV on 5 boys aged 10 to 13 (11.8 ± 1.1) years diagnosed with ASD according to Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition . Results: The RSV treatment significantly reduced the Aberrant Behavior Checklist total score ( P = 0.042) and Irritability ( P = 0.041), with no alteration in Stereotypical Behavior ( P = 0.066), Hyperactivity ( P = 0.068), and Lethargy/Social Withdrawal ( P = 0.078) subscales. On the Clinical Global Impression scale, 3 individuals showed marked improvement in behavior; one showed mild improvement, and the other had no changes. The RSV treatment increased the miR-195-5p ( P = 0.043), an important modulator of targets related to inflammatory and immunological pathways. RSV administration did not present adverse effects and did not alter clinical laboratory results. Conclusions: RSV is a safe molecule for administrating in the pediatric population, able to modulate behavior alterations and molecules associated with the immune system, becoming a promising therapeutic strategy for large-scale studies in ASD, to investigate both behavioral and molecular approaches.